Harnessing the PD-L1 interface peptide for positron emission tomography imaging of the PD-1 immune checkpoint. Issue 4 (27th August 2020) - Hu, Kuan; Xie, Lin; Hanyu, Masayuki; Zhang, Yiding; Li, Lingyun; Ma, Xiaohui; Nagatsu, Kotaro; Suzuki, Hisashi; Wang, Weizhi; Zhang, Ming-Rong
Abstract : Leveraging interface peptides in PD-L1 for PET imaging of PD-1, providing a new paradigm for radiotracer development. Abstract : Interface peptides that mediate protein–protein interactions (PPI) are a class of important lead compounds for designing PPI inhibitors. However, their potential as precursors for radiotracers has never been exploited. Here we report that the interface peptides from programmed death-ligand 1 (PD-L1) can be used in positron emission tomography (PET) imaging of programmed cell death 1 (PD-1) with high accuracy and sensitivity. Moreover, the performance differentiation between murine PD-L1 derived interface peptide (mPep-1) and human PD-L1 derived interface peptide (hPep-1) as PET tracers for PD-1 unveiled an unprecedented role of a non-critical residue in target binding, highlighting the significance of PET imaging as a companion diagnostic in drug development. Collectively, this study not only provided a first-of-its-kind peptide-based PET tracer for PD-1 but also conveyed a unique paradigm for developing imaging agents for highly challenging protein targets, which could be used to identify other protein biomarkers involved in the PPI networks.